(untitled) (Jurnal Bawaslu Provinsi Kepulauan Riau, 2023)
The 2024 general elections are just around the corner. Still, there is strong momentum, especially in cases against the Constitutional Court overhauling the implementation of an open proportional system in the 2024 elections. This short article aims to ascertain to what extent open and closed proportionality systems enhance the quality of political representation in Indonesian elections. Use a qualitative research approach and secondary data as the primary source. Independent of the debate between public and closed proportional representation systems, provided that there are still many monetary policy practices, weak political representation, and unclear ideological positions of political parties. He said that a mixed system of closed proportional representation at the national level combined with open proportional representation at the state and county/city levels simultaneously addressed two issues, the quality of political representation and the enhancement of publicity.